Imaging in Clinical Oncology (Springer International Publishing, 2018)
This is the second edition of a well-received book reflecting the state of the art in oncologic imaging research and promoting mutual understanding and collaboration between radiologists and clinical oncologists. It presents all currently available imaging modalities and covers a broad spectrum of oncologic diseases for most organ systems. Today, oncologic imaging faces the challenge of improving and refining concepts for precise tumor delineation and biologic/functional tumor characterization, as well as for purposes of creating individual treatment plans. The concept of radiomics has further advanced the conversion of images into mineable data and subsequent analysis of said data for decision-making support. Since the release of the book's first edition, radiomics has been introduced in oncology studies and can be performed with tomographic images from CT, MRI and PET/CT studies. The combination of radiomic data with genomic features is known as radiogenomics, and can potentially offer additional decision-making support. This book will be of interest to clinical oncologists with regard to the diagnosis, staging, treatment and follow-up on various tumors affecting the CNS, chest, abdomen, urogenital and musculoskeletal systems.